Influence of thermal history on the mechanical properties of poly(ether ketone ketone) copolymers. (21st August 2019) - Choupin, Tanguy; Debertrand, Louis; Fayolle, Bruno; Régnier, Gilles; Paris, Christophe; Cinquin, Jacques; Brulé, Benoît
Abstract: Since poly(ether ketone ketone) (PEKK) is a good candidate as a matrix for composite structural parts, the mechanical properties of PEKK copolymers prepared from diphenyl ether, terephthalic acid (T), and isophthalic acid (I) with different T/I ratios were assessed at room temperature and above their glass transition temperature depending on the thermal history during processing. The influence of cooling conditions and macromolecular modifications at high exposure temperatures was investigated. Results show that modulus and yield properties for a given testing temperature follow a master curve driven mainly by crystallinity regardless of the PEKK copolymers. By modifying PEKK during exposures at 400°C, which leads to branching mechanisms before crystallization, it is shown that modified PEKKs follow the master curve, thus confirming the predominant role of crystallinity in small deformation properties. However, for some morphologies, depending on the crystallization conditions such as cold or melt crystallization, a slight deviation is observed from the global master curve. Abstract : The authors propose an investigation of tensile properties of new commercially available poly(ether ketone ketone) copolymers (Arkema). By modifying terephthaloyl and isophthaloyl isomer ratios and crystallization conditions, a large range of crystallinity is attainable experimentally. As a result, the authors highlight a master curve describing crystallinity and tensile properties such as modulus and yield stress.